Electrochemical training of nanoporous Cu-In catalysts for efficient CO2-to-CO conversion and high durability. (1st February 2019) - Barasa, Godfrey Okumu; Yu, Tianshui; Lu, Xianglong; Zhou, Xiangji; Wang, Hailing; Qian, Lihua; Yu, Yao; Liu, Lin; Lei, Pengxiang
Abstract: Electrochemical carbon dioxide (CO2 ) reduction into valuable chemicals is usually implemented at high overpotential, and most bimetallic catalysts suffer from the dramatic evolution of surface composition especially in case of long-term operation. In this work, as a proof-of-concept experiment, one effective protocol is first identified to drive the positive evolution of surface contents on nanoporous Cu-In by electrochemical training in KHCO3 electrolyte. Interestingly, superior performances including high selectivity for CO production and robust reliability are realized. Thus, Faradaic efficiency can approach the maximum of 91% at −0.95 V ( vs . RHE), and an excellent durability can be simultaneously testified by no detectable performance decay for 7 h in operation. More importantly, current investigation paves a new road for designing bimetallic electrocatalysts with high selectivity and long-term durability.